Implementation of QPSK transmission scheme on FPGA board / Mohd Fisoel Haron - Haron, Mohd Fisoel (2013)
This project aims to implement the QPSK transmission scheme using Field - Programming Gate-Array (FPGA) method. This project scope includes studying verilog codes, using FPGA Xilink software and implemented on FPGA board.